PENGARUH IMPLEMENTASI KEBIJAKAN PAGU INDIKATIF KEWILAYAHAN TERHADAP EFEKTIVITAS PROGRAM MUSRENBANG DI KABUPATEN SUMEDANG (Studi Kasus Kecamatan Buahdua): - Dadang Suryana; Deden Haria Garmana (Program Studi Ilmu Pemerintahan FISIP Universitas Galuh, 2026)
This study aims to determine the effect of the implementation of the Regional Indicative Budget Ceiling Policy on the effectiveness of achieving the priority objectives of the Musrenbang program in Sumedang Regency, using a case study in Buahdua District. This research was conducted using a quantitative method, based on the philosophy of positivism, with the aim of testing the established hypotheses. In this study, the researcher employed descriptive inferential data analysis techniques to describe the collected data as it is and draw generally applicable conclusions. The sampling technique used was saturated sampling, with a population of 30 individuals. Based on the research results, the implementation of the Regional Indicative Budget Ceiling Policy in Bauhdua District, Sumedang Regency, reached 70.33% of the ideal criteria, with a total score of 2110, categorized as Poor. Similarly, the effectiveness of the program in achieving the priority objectives of the Musrenbang program in Buahdua District, Sumedang Regency, reached 76.1% of the ideal criteria, with a total score of 2283, categorized as Good. The correlation between the implementation of the Regional Indicative Budget Ceiling Policy and the effectiveness of the program in achieving the priority objectives of the Musrenbang program in Buahdua District is very strong, with a correlation coefficient of 0.94, categorized as strong. Meanwhile, the impact of the implementation of the Regional Indicative Budget Ceiling Policy on the effectiveness of the program in achieving the priority objectives of the Musrenbang program in Buahdua District is 89.30%, while the remaining 10.7% is influenced by other factors (epsilon) that influence program effectiveness. Keywords: Policy Implementation, Indicative Ceiling, Program Effectiveness.